Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T00:19:50+01:00
(0,6)do -8 *(1 2/3 )do -8
=(3/5)⁻⁸ *(5/3)⁻⁸= ( POTĘGA 8)
=(5/3)⁸ *(5/3)⁻⁸ = (5/3)° = 1

(3,75)do -3 * (1,6) do -3
(15/4)⁻³ *(8/5)⁻³=[(15/4)(8/5)]⁻³ = 6⁻³ = (1/6)³ =( 1/216)

( 7/9 )do -2 * (4,5) do -2
(7/9)⁻²*(9/2)⁻² = [(7/9)(9/2)]⁻² = (7/2)⁻² = (2/7)² = (4/49)

(2,4)do -3 :(0,6)do -3
(12/5)⁻³ : (3/5)⁻³ = [(12/5):(3/5)]⁻³ = 4⁻³ = (¼)³ = (1/64)

(,2) do -2 :(0,5 )do -2 PRZYPUSZCZAM ŻE BRAKUJE "0" NA POCZĄTKU
(1/5)⁻² :(½)⁻² = [(1/5):(½)]⁻² =(2/5)⁻² = (5/2)² = 25/4 = 6¼

(3,6) do -3 :(0,9)do -3
(18/5)⁻³ : (9/10)⁻³ = [(18/5):(9/10)]⁻³ = 4⁻³ = (¼)³ = (1/64)